2011
DOI: 10.1002/ppap.201000123
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of SIFT‐MS and PTR‐MS Experiments to Explore Reaction Mechanisms in Plasmas of Volatile Organics: Siloxanes

Abstract: Selected ion flow tube mass spectrometry (SIFT‐MS) and proton transfer reaction mass spectrometry (PTR‐MS) are used to explore ion‐molecule reactions in low temperature and pressure plasmas of hexamethyldisiloxane. These techniques shed new light on possible reactions taking place within such plasma environments and validate many of the reaction pathways previously advocated based upon plasma‐phase MS. However, SIFT‐MS and PTR‐MS results draw attention to the possible importance of the H3O+ ion in initiating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
2
12
1
Order By: Relevance
“…In this study, the Si 2 OC 4 H 11 + ion was not observed. In a SIFT-MS and PTR-MS study,106 it was shown that in SIFT-MS, the main reaction channel results in the ion at m/z 147.066, whereas in PTR-MS, at an E/N of 140 Td, the main ion occurs at m/z 149.045, which is in agreement with our findings. The reaction channel producing the ion at m/z 149.045 corresponds to the exchange of a methyl group for an OH…”
supporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the Si 2 OC 4 H 11 + ion was not observed. In a SIFT-MS and PTR-MS study,106 it was shown that in SIFT-MS, the main reaction channel results in the ion at m/z 147.066, whereas in PTR-MS, at an E/N of 140 Td, the main ion occurs at m/z 149.045, which is in agreement with our findings. The reaction channel producing the ion at m/z 149.045 corresponds to the exchange of a methyl group for an OH…”
supporting
confidence: 92%
“…It remains unclear which compounds contribute to this signal, because C 7 H 7 + does not correlate with toluene and for trimethylsilanol and diethyl sulfide a differentiation cannot be made. The ion at m/z 91 has been reported to be the result of the association of the (CH 3 ) 3 Si + ion ( m/z 73.047) with water, 106,107 which here was incommensurable and, if present, the small signal overlapped with the water cluster [(H 2 O) 3 ]H 3 O + . In SIFT‐MS measurements using H 3 O + , trimethylsilanol was shown to give the ion at m/z 91.057, and in the presence of water, it converts to (CH 3 ) 2 SiOH.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A substantial level of absorption intensity for the Si(CH 3 ) 2 structure (800 cm -1 ), which does not exist in the HMDSO monomer structure, indicated that the plasma-deposited HMDSO-film was mainly composed of the dimethyl-siloxane backbone formed in the plasma-induced cationic polymerization. [29] A weak peak at 1350 cm -1 might be ascribed to the CH 2 scissoring and wagging vibrations in Si-CH 2 -Si. [30] The signal for Si-CH 2 -Si at 1350 cm -1 was reported to be very weak, and was usually observed with a much stronger absorption due to the wagging vibrations of CH 2 at around 1060 cm -1 .…”
Section: ---mentioning
confidence: 99%
“…or floating (self‐biased) as in Ref 52. A number of bulk gas‐phase ion–molecule reaction schemes have been proposed on this basis,51, 53 and several of these have been validated using a selected ion flow tube (SIFT) experiments,54, 55 or substantially revised, particularly in the light of the generation of molecular ions by charge transfer from H 3 O + 56…”
mentioning
confidence: 99%